2014
DOI: 10.5897/ijeaps12.036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Leadership styles on Teachers job satisfaction: A case of selected Primary Schools in Songea and Morogoro Districts, Tanzania

Abstract: This study reports on the kind of school leadership style that best suits for promoting teachers' job satisfaction in primary schools in Tanzania. The study employed cross sectional research design with samples of 200 teachers from 20 selected primary schools in Songea and Morogoro districts. Interviews, documentary analysis and questionnaires were used to collect data. The data were analyzed both qualitatively and quantitatively using tables, frequencies and percentages. It was found that the democratic leade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…In other words, there is sameness or semblance in the leadership style of choice or preference in both locations as found by the two studies. Also, this finding of the study is in line with the submission of Haruni and Mafwimbo (2014), which asserted that the democratic leadership style was the most dominant leadership style among school heads in primary schools. They noted that there was much to be learnt from the democratic leadership style in low-performing primary schools.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In other words, there is sameness or semblance in the leadership style of choice or preference in both locations as found by the two studies. Also, this finding of the study is in line with the submission of Haruni and Mafwimbo (2014), which asserted that the democratic leadership style was the most dominant leadership style among school heads in primary schools. They noted that there was much to be learnt from the democratic leadership style in low-performing primary schools.…”
Section: Discussionsupporting
confidence: 87%
“…Among other findings, it was found that the democratic leadership style was the most commonly used leadership style among principals of senior secondary schools in the state. Haruni and Mafwimbo (2014) investigated the influence of leadership styles on teachers' job satisfaction in Songea and Morogoro Districts, Tanzania. The study employed a cross-sectional research design, with samples of 200 teachers from 20 selected primary schools in Songea and Morogoro Districts.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in accordance with prior research on faculty staff perceptions of leaders' capabilities. As Haruni & Mafwimbo (2014) reported that, faculty staff were able academic leaders. On the contrary Simsek & Gozukara (2016) found that faculty staff had fair level of leadership capabilities.…”
Section: Discussionmentioning
confidence: 98%
“…In recent times retaining and motivating the workforce has become quite challenging due to the intense competitive situation around the world. Educational leaders play important role with the intention to make teaching and learning more effective and to give quality education to students (Haruni & Mafwimbo, 2014). Establishing a positive relationship between Head of Department and their staff is a very important strategy in educational leadership.…”
Section: Introductionmentioning
confidence: 99%
“…Leadership style refers to the underlying need structure of the principal that motivates his/her behavior in various leadership situation (Okumbe, 2007). A study in Tanzania by Haruni and Mafwimbo(2014) supported that school leaders are supposed to possess ability of influencing their staffs, parents and other stakeholders of education to make sure their schools successfully attain it preintended objectives by making sure their teachers perform their responsibilities well and learners perform well in their academic as anticipated. Mpokosa and Ndaruhutse (2008) found that lack of job dissatisfaction results in absenteeism, poor utilization of class time, professional misconduct, traditional teaching methods, poor preparation and secondary income generating activities that distract teaching duties.…”
Section: Introductionmentioning
confidence: 99%